Health and innovation: economic dynamics and Welfare State in Brazil - Carlos Augusto Grabois Gadelha; Patrícia Seixas da Costa Braga
Abstract: The effective enforcement of the access to healthcare as fundamental right requires an important theoretical and political effort at linking the often contradictory economic and social dimensions of development. This study suggests the need for a systemic view of policies related to the industrial base and innovation in health and the construction of the Brazilian Unified National Health System (SUS). The authors investigate the relations between health, innovation, and development, seeking to show and update the political, economic, and social determinants of the recent Brazilian experience with the Health Economic-Industrial Complex (HEIC). They discuss how the agenda for innovation and domestic industrial production in health gained a central place in the project for construction of the SUS. The article thus seeks to link inherent issues from the agenda for development, production, and innovation to social policy in healthcare, as observed in recent years, and based on this analysis, points to political and conceptual challenges for implementing the SUS, especially as regards strengthening its technological and industrial base. As a byproduct, the article develops an analytical and factual focus on the consolidation of the HEIC in Brazil, both as a dynamic vector of industrial development, generating investment, income, employment, and innovations, and as a decisive element for reducing vulnerability and structural dependence in health. The authors aim to show that strengthening the SUS and orienting it to social needs is an essential part of building a social Welfare State in Brazil.